Ultrasound-guided microwave ablation for the treatment of idiopathic granulomatous mastitis: comparison with surgical excision - Hang Li; Guoliang Zhang; Hongling Wang; Haiying Chen; Xiaoli Liu; Chuansheng Zheng; Lisheng Lin; Lihong Li (BMC, 2024)
Abstract Background Idiopathic granulomatous mastitis (IGM) results in notable clinical symptoms and breast deformity. This study aimed to evaluate the clinical feasibility of microwave ablation (MWA) for the treatment of IGM through comparison with surgical excision. Methods From June 2016 to December 2020, a total of 234 consecutive patients admitted to the hospital were retrospectively included in this study. IGM was pathologically confirmed via breast biopsy in all included patients. These patients were divided into the MWA group (n = 91) and surgical group (n = 143) based on the type of treatment. Patients in both groups received oral prednisone prior to intervention. The clinical remission rate, recurrence rate, operative pain, complications, and BREAST Q score were compared between the two groups. Results There were 340 lesions in the MWA group, and 201 lesions in the surgical group were ultimately included. Significant differences in the complete remission rate (96.7% vs. 86.7%, p = 0.020), recurrence rate (3.3% vs. 13.3%, p = 0.020), operation time (48.7±14.6 min vs. 68.1±36.4 min, p < 0.001), postoperative pain (p < 0.001) and postoperative BREAST Q score (p < 0.001) were observed between the MWA and surgical groups. Conclusions Microwave ablation is feasible for the treatment of IGM, due to its high curative rate and low recurrence rate. Because of the minimal invasiveness of MWA and sufficient preservation of the gland and contour of the breast, patients are more satisfied with the appearance of the breast. Therefore, for patients with complex conditions requiring surgery, MWA is a good alternative treatment.